Acidic buffering capacity and curing process of melamine-urea-formaldehyde resin. (January 2021) - Ding, Zhongjian; Ding, Zhongqiang; Ma, Tianlin; Zhang, Hua
Abstract: In this work, melamine-urea-formaldehyde (MUF) resins with different melamine levels added at different stages were synthesized. The acidic buffering capacity and gel time of the MUF resins were measured. The curing behaviour of MUF resins with different acidic buffering capacities was studied by differential scanning calorimetry (DCS). The morphology of the cured MUF resins was obtained by a scanning electron microscope. The results show that the acidic buffering capacity of MUF resin increases with the alkalinity increment of melamine derivatives in the MUF resin. The acidic buffering capacity and condensation reactivity of the MUF resin jointly affect the gel time of the MUF resin. The lower the reactivity of the MUF resin was, the greater the influence of the acidic buffering capacity on gel time. The higher the reactivity of the MUF resin was, the smaller the influence of the acidic buffering capacity on gel time. The addition of melamine to the MUF resin enhanced the degree of cross-linking of cured MF and MUF components in the MUF resin but weakened the degree of cross-linking of the cured UF component under the same curing environment.